Distribution and promotion network as an effort to increase sales in the home industry of Fish Crackers in Pesawaran Lampung - sunarmi sunarmi; Andi Mulyono; Makhda Intan Sanusi (Junal Ilmu Manajemen, 2023)
Homes Industrial Company Fish Crackers Rafa’s Cracker 002in Kahuripan Sidodadi Waylima village, Pesawaran Regency is one of the small industries engaged in the industry of making food ingredients in the form of Fish Crackers. In its activities so far, the industry has faced ups and downs in its marketing. This is due to various factors, especially competition from similar businesses that began to mold in some regions so that it affected the amount of production and sustainability of this business. Business competition is gettingtighter, making business owners rack their brains harder so that the business continues to run and is still able to bind customers so as not to move to other competing products that offer more competitive prices. This study aims: 1). To find out the concept of distribution and promotion networks in an effort to increase sales at the Rafa’s Fish Cracker Home Industry 002 Pesawaran, 2). To find out how the distribution and promotion network is ideal in increasing sales at the Rafa’s Fish Cracker Home Industry 002 Pesawaran. This study uses a qualitative descriptive method, namely field research on research objects where data collection is carried out by conducting direct research by conducting direct interviews with business owners. Research Results: 1). The Rafa’s Fish Cracker Home Industry 002 Pesawaran, applies indirect distribution, namely from producers to agents from agents to wholesalers from wholesalers to retailers then from retailers to consumers, where this indirect distribution is also used as a promotional medium to increase sales, 2). Increased sales will affect the amount of production, so that business owners place more emphasis on promotions carried out through the distribution network. However, this fish cracker product is well known and much in demand by the people in Lampung and its surroundings.